Schaeffler KG/ Continental AG im Lichte der CSX Corp.-Entscheidung des US District Court for the Southern District of New York: Meldepflichten bei öffentlichen Übernahmen und deren Umgehung durch Einsatz von derivativen Finanzinstrumenten - Kay-Michael Schanz (Frankfurt School of Finance & Management, 2008)
This report analyses the possibility to outflank disclosure obligations under the German Securities Trading Act as well as the German Takeover Act by using derivative instruments in the context of the attack of Schaeffler KG on Continental AG. Irrespective of a limited knowledge of the complete facts it comes to the conclusion that, under certain conditions, there are good reasons to assume violations of legal obligations that would entitle the Federal Financial Supervisory Authority to fix hefty fines but not to prohibit the offer.
urn:nbn:de:101:1-2008091202
Keywords: K12; K19; K22; K29; 330; Public takeovers; hostile takeovers; notification requirements; cash-settled equity total return swaps; cash swaps; equity options; options; mandatory offer; insider trading; capital markets; regulated markets; tender offer; tender offer rules; announcement obligations; securities trading act; takeover act; Schaeffler; Contigummi; Continental; BaFin; Bundesanstalt für Finanzdienstleistungsaufsicht; CSX; The Childrens Investment Fund Management; TCI